MOHAMMAD HATTA DAN SOSIALISME ISLAM - Maula Husein Mahfud (Qurthuba: The Journal of History and Islamic Civilization, 2019)
Abstract: This article is about thinking Mohammad Hatta on Islamic socialism. The problems that are the object of his study include, (1) What are the reasons behind the birth of the thought of Islamic Socialism in the view of Mohammad Hatta (2) Who are the national figures who have thoughts of Islamic Socialism (3) What is the concept of Islamic Socialism in Mohammad Hatta's thought and its influence on Indonesian nation. The research method used in this thesis is a historical research method consisting of heuristic, verification, interpretation and historiography stages. Meanwhile, the concept/theory used in this study is Wilhem Dilthey's theory in his book Pattern and Meaning in History. The results of this study indicate that: (1) The background to the emergence of Islamic Socialism in Mohammad Hatta was influenced by his family, education and struggle to liberate Indonesia. Born into a family of scholars' who taught moral and social values. (2) National figures who have the idea of ​​Islamic Socialism are HOS Tjokroaminoto and Haji Agus Salim. The idea of ​​Islamic socialism from these two figures is an attempt to present that the teachings of Islam contain social values ​​which in the end are equality and equality. (3) The idea of ​​Islamic socialism that belongs to Mohammad Hatta is an attempt to relevance social values ​​in the teachings of Islam with the concepts of Socialism. Keywords: Mohammad Hatta, Islamic socialism, Islamic religion, ideology